Childhood Adversity, Socioeconomic Instability, Oxytocin-Receptor-Gene Methylation, and Romantic-Relationship Support Among Young African American Men. (August 2019) - Kogan, Steven M.; Bae, Dayoung; Cho, Junhan; Smith, Alicia K.; Nishitani, Shota
Men's emerging adult romantic relationships forecast downstream relationship behavior, including commitment and quality. Accumulating evidence implicates methylation of the oxytocin-receptor-gene ( OXTR ) system in regulating relationship behavior. We tested hypotheses regarding the links between (a) childhood adversity and (b) socioeconomic instability in emerging adulthood on supportive romantic relationships via their associations with OXTR methylation. Hypotheses were tested using path analysis with data from 309 participants in the African American Men's Project. Consistent with our hypotheses, results showed that OXTR methylation proximally predicted changes in relationship support during a 1.5-year period. Childhood adversity was not directly associated with OXTR methylation but, rather, with contemporaneous socioeconomic instability, which in turn predicted elevated OXTR methylation. Findings suggest that early adversity is indirectly associated with OXTR methylation by links with downstream socioeconomic instability. Findings must be considered provisional, however, because preregistered replications are needed to establish more firmly the relations among these variables.